PERAN MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KERJA MENURUT PERSPEKTIF ISLAM - Sugianto, Imam; Yulia, Rahma; Rokhmawati, Dian (Arthavidya Jurnal Ilmiah Ekonomi, 2020)
Abstract: The role of Islamic human resource management isconsidered to significantly influence employee performance. BankBRI Syariah branch of Pakis Malang implements Islamic-basedhuman resource management. The study was conducted todetermine the role of Islamic-based human resource management onemployee performance using descriptive qualitative approach. Theindicators of employee performance are moral values, compensation,spirituality, organizational systems and structures, work quality,creativity and cooperation. As a financial institution that refers toIslamic principles, Bank BRI Syariah branch of Pakis Malang has anIslamic culture that is applied in its human resource management.The implementation of Islamic cultural values to human resourcemanagement at BRI Syariah branch of Pakis Malang, employeesbecome more enthusiastic at work because they feel that their workis a form of worship, being a motivation and a boost for employeeperformance.Keywords: Islamic Human Resource Management, EmployeePerformance, BRI Syariah